Orthopedic treatment in cancer patients with maxillofacial pathology - I. V. Pustovaya; M. A. Engibaryan; P. V. Svetitskiy; I. V. Aedinova; V. L. Volkova; N. A. Chertova; Yu. V. Ulianova; M. V. Bauzhadze (Южно-Российский онкологический журнал, 2021)
Relevance. Staged orthopedic treatment was used to improve the quality of life of patients who underwent radical maxillofacial surgeries for cancer.Patients and methods. 197 patients receiving treatment for maxillofacial cancer were observed at the Department of head and neck tumors, National Medical Research Centre for Oncology of the Ministry of Health of Russia, in 1998- 2018. All patients underwent radical surgical treatment resulting in postoperative defects of the upper jaw, soft tissues of the zygomatic- buccal-orbital region, nose, or auricle.Results. Removable obturator prostheses with various supporting and retaining elements were made for 159 (80.7 %) patients. Individual facial prostheses were made for 38 (19.3 %) patients: 17 (44.7 %) – external orbital prostheses, 14 (36.8 %) – external nasal prostheses, 6 (15.8 %) – external zygomatic- buccal-orbital prostheses, 1 (2.7 %) – external auricle prosthesis. Combined prostheses were made for 4 patients– removable upper jaw obturator and nose prosthe[1]sis; removable upper jaw obturator and eye prosthesis. Combined prostheses were fixed to each other using magnets. The results of maxillofacial prosthetics were evaluated according to the aesthetic requirements of the patients and their quality of life. Maxillofacial prostheses allowed a complete restoration of chewing, swallowing, and speaking, restored facial deformation, and improved the appearance of patients.Conclusions. Timely and comprehensive orthopedic treatment of patients with postoperative maxillofacial defects after radical surgeries for malignant tumors takes the main place in the complex of rehabilitation measures. Early elimination of extensive defects is aimed at maximum restoration of oral dysfunctions and appearance preservation. The apparent advantages of maxillofacial prostheses involve improvement of social adaptation and the quality of life of patients, which promotes complete rehabilitation and a return to socially useful activities.